Evaluation of apical seal and tubular penetration of a novel bioactive glass sealer, bioceramic sealer and resin–based sealer: an In-Vitro study - M. Bilal; S. Pasha; S. Kumar; S. Arif; S. Taj; A. Saleem (Эндодонтия Today, 2025)
INTRODUCTION. The majority of endodontic failures are caused primarily by inadequate sealing of the root canal. Seepage of fluids is likely to occur if apical seal is not properly established.AIM. This in-vitro study was to evaluate the apical seal and tubular penetration of a novel bioactive glass sealer:NISHIKA CANAL SEALER BG, bioceramic sealer: CERASEAL and epoxy resin–based sealer: AH PLUS.MATERIALS AND METHODS. 49 extracted human single rooted mandibular 1st premolar teeth with fully formed apices were taken and decoronated at the Cemento Enamel Junction for standardized working length of 14 mm. All samples were instrumented upto size F3 of ProTaper Gold files. After complete irrigation protocols with Sodium Hypochlorite, Saline, Ethylene diamine tetra acetic acid and Chlorhexidine, samples were divided into 3 groups according to the sealers used. Obturation was done using single cone technique. All the specimens were put in 1% methylene blue dye for 72 hours after keeping them in incubator for 48 hours. Teeth were split into two halves, one visualised for dye penetration and other for tubular penetration and scoring was done.RESULTS. Kruskal Wallis test revealed that there were significant differences in microleakage and tubular penetration between all the groups (p = 0.01). Nishika Canal Sealer BG had better apical sealing ability and tubular penetration followed by CeraSeal and AH Plus.CONCLUSIONS. Within the limitations of the study, it was concluded that, Nishika Canal Sealer BG has the maximum apical sealing ability and tubular penetration when compared to CeraSeal and AH Plus